PECAHAN TEMPURUNG KELAPA SEBAGAI AGREGAT KASAR PADA BATAKO - Subehan; Lilis Indriani (Jurnal Informasi, Perkebunan dan Sipil, 2021)
The addition of other materials, especially natural fibers in normal concrete, certainly has its own way of analysis. The addition and in certain proportions may affect the behavior of the concrete structure as a whole. The effect of this change needs to be investigated to provide accurate information about the behavior and capacity of fibrous concrete, especially palm fiber. This study was to determine whether the addition of nipa fruit fibers increased the compressive strength of normal concrete mixtures, to determine the optimum level of addition of nipa fruit fibers that could affect the compressive strength of normal concrete. The compressive strength of concrete has increased with the addition of palm fiber as a substitute for some of the volume. The compressive strength of concrete with a variation of 0% is 19.640 MPa, a variation of 0.2% is 15,648 MPa, a variation of 0.4% is 11.875 MPa and a variation of 0.6% is 7.224 MPa. Partial replacement of nipah fruit fibers in the concrete mixture gave an increase in the compressive strength of concrete at 28 days with a variation of 0.2%. The design compressive strength fc' = 13.53 MPa while the resulting compressive strength is 15.648 MPa or an increase of 13.535%.